Can serum ferritin levels predict the severity of dengue early?: an observational study - Petchiappan, Velammal; Hussain, Thaha Mohammed; Thangavelu, Saravanan (International Journal of Research in Medical Sciences, 2019)
Background: Dengue infection is a major public health threat; early recognition is crucial to improve the survival in severe dengue. Although there are various biomarkers to predict the severity of dengue, they are not routinely used in clinical practice for prognostication. We analyzed whether serum ferritin can be used to predict the severity at an earlier stage. Methods: A hospital based prospective observational study was done involving 119 dengue cases diagnosed by positive NS1 antigen or dengue specific serology (capture ELISA). Serum ferritin was measured in all at the time of diagnosis. Clinical and platelet count monitoring was done daily; classified as severe and non-severe according to 2009 WHO criteria. Results: Out of 119, 5 developed severe dengue; patients with severe dengue had significantly lower median platelet count (p<0.0001); higher ferritin levels (p=0.03) and hospital stay (p<0.0001) than non-severe group. Age had a significant negative co-relation with platelet count (r= -0.427; p<0.0001); positive correlation with ferritin levels (r=0.16; p=0.08) and hospital stay (r= 0.26; p=0.004) indicating that elderly subjects are at risk of severe disease. Serum ferritin levels negatively correlated with the platelet count (r= -0.51 p<0.001). High ferritin levels in severe cases are noted from day 4 of clinical illness. Conclusions: Elevated serum ferritin levels can be used as a potential early prognostic marker to predict the severity of dengue infection in clinical practice.